PENGARUH FAKTOR SOSIAL, EKONOMI DAN DEMOGRAFI TERHADAP PENDAPATAN USAHA SEKTOR INFORMAL DI DESA DARMASABA - I Made Sedana Putra; I Ketut Sudibia (PIRAMIDA, 2018)
Various efforts can be made to increase household income, one of them through family contribution to theinformal sector. The purpose of this study is to analyze the influence of education level, marital status and thenumber of dependents on the work hour and income in the informal sector in Darmasaba village, Badung regency.Research sample is informal sector business actors, as many as 82 respondents. Sampling was done by nonprobabilitysampling, accidental and snowball sampling. The analysis technique used is path analysis with hourly working houras intervening variable. The results showed that education level, marital status and the number of dependents havea positive and significant effect on the outpouring of the working hours. The level of education, the number ofdependents and the outpouring of working hours has a positive and significant impact on income. Meanwhile, maritalstatus indicates there is no difference of income between married and unmarried status. The level of education,marital status and the number of dependents indirectly have a significant effect on income through hourly hours.